PENINGKATAN KETERAMPILAN MENULIS KARANGAN MELALUI MEDIA GAMBAR SERI PADA SISWA KELAS IV SD TAHUN AJARAN 2022/2023 - Jamilah; Nurasiah, Iis; Nurmeta, Irna Khaleda (PREMIERE : Journal of Islamic Elementary Education, 2023)
Essay writing skills, especially descriptive text essays, are still relatively low for grade IV students at SD. This problem requires a solution so that students' essay writing skills will increase. The purpose of this study is to determine the planning, implementation, and improvement of essay writing skills through the use of picture series media. The subjects of this study were 24 grade IV students at SD. The study used a class action research design by Kemmis and Mc Taggart. Data was collected through tests, observations, and documentation and then analyzed using descriptive statistical techniques. The results showed that students' ability to write essays, especially descriptive texts, increased by using picture series. After learning using picture series students can describe objects completely and clearly then in writing descriptive text students can also write them using good grammar and use correct punctuation and spelling. From the results of the assessment it was found that in the pre-cycle the average value obtained was 67.26 and was included in the criteria of being quite capable. Then in cycle I there was an increase of 11.31 so that the average value obtained was 78.57 and included in the capable criterion. In cycle II it increased again by 11.01 so that in cycle II the average value obtained was 89.58 and it was included in the very capable criteria.